Pengenalan Benda-benda Bersejarah Museum Fatahillah Melalui Pemanfaatan Media Animasi Interaktif Untuk Anak Sekolah Dasar - Ummi Ulfah; Syarif Hidayatulloh (JURNAL TEKNIK KOMPUTER, 2019)
- Interactive animation is a learning media that is quite interesting for children. This is because learning how to use animation is not difficult and more fun for elementary school children than learning to use printed picture books or encyclopedias. This interactive animation was created to introduce Fatahillah museum objects to children. This animation was made to provide knowledge for children about objects in the Fatahillah museum. In addition, this can also be a more interesting and new learning method for school children. In developing existing material, in this study three methods of data collection techniques will be used including observation, interviews and literature. Then for the system development model, it has been tested using software requirements analysis, design, coding, testing, and support. In this study also used some software to build interactive animations to be created including Adobe Flash CS 3 and Adobe Photoshop CS 6. The results of the analysis showed that the introduction process through interactive animation media had a major influence in improving the understanding of elementary school children about introductory material object of Fatahillah museum, this is because children's understanding will be better with explanations that use images, sound effects, and visuals.